2008
DOI: 10.1016/j.cub.2008.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Phase Resetting of the Mammalian Circadian Clock by DNA Damage

Abstract: To anticipate the momentum of the day, most organisms have developed an internal clock that drives circadian rhythms in metabolism, physiology, and behavior [1]. Recent studies indicate that cell-cycle progression and DNA-damage-response pathways are under circadian control [2-4]. Because circadian output processes can feed back into the clock, we investigated whether DNA damage affects the mammalian circadian clock. By using Rat-1 fibroblasts expressing an mPer2 promoter-driven luciferase reporter, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 33 publications
9
102
0
Order By: Relevance
“…Several studies have demonstrated that external stimuli, such as ionizing radiation, UV light, and hydrogen peroxide affect circadian gene expression by cultured cells and tissues (34,35). We have also confirmed that hydrogen peroxide altered circadian gene expression and the accumulation of PER2 protein (supplemental Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have demonstrated that external stimuli, such as ionizing radiation, UV light, and hydrogen peroxide affect circadian gene expression by cultured cells and tissues (34,35). We have also confirmed that hydrogen peroxide altered circadian gene expression and the accumulation of PER2 protein (supplemental Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Of the many processes being regulated by the circadian clock, some of the most profound are those related to specific cell-cycle events, DNA repair, and apoptosis (2,4,5,(21)(22)(23)(24)(25). The dynamics of the coupling we describe here are likely to be controlled through multiple and interacting pathways.…”
Section: Discussionmentioning
confidence: 97%
“…19,20) However, the physiological role of SCN-independent responses of peripheral clocks is not yet fully understood. A recent study has reported that DNA damage can also act as a resetting cue for the circadian clock in mammalian peripheral cells, 21) and other findings support a major role for the circadian machinery in cellular stress responses. 22) These data point to an intriguing link between the circadian clock and cellular stress responses, and it is the purpose of this review to summarize the evidence and explore the implications of such a link.…”
Section: Introductionmentioning
confidence: 92%